The Effects on the Bracing Stiffness of Timber Structures of the Stiffness of Its Members. (June 2019) - Klasson, Anders; Crocetti, Roberto
Abstract: The design of slender structures is often associated with a number of assumptions made by engineers in checking on the stability of the structure. Not seldom, these assumptions are rather uncertain. In the present paper the effects of the stiffness of different members on the bracing stiffness of timber structures is studied. Both full-scale laboratory testing and FE-modelling are employed here in the investigation. In particular, two different bracing approaches are analysed, those of (1) cross bracing (wind trusses) and (2) diaphragm action (through use of steel sheeting) in the plane of the roof. In addition, the effects of the connections and the number of fasteners used in the structure are evaluated. The stiffness of the connections is obtained by means of an FE-updating approach, i.e. that the relevant parts included in the FE-model are calibrated to ensure that the FE-results match the laboratory results. The findings obtained indicated, (1) that the connections can have a significant effect on the stiffness of the bracing systems, (2) that the cross bracings close to the mid-span of the structure are less effective than those close to the supports, (3) that the lateral stiffness obtained using a diaphragm approach is closely related to the number of fasteners between the steel sheet and the timber parts in the roof that are employed, and (4) that the two different bracing approaches used provide about the same lateral stiffness of the roof. Finally, it should be emphasized that FE-models can markedly overestimate the stiffness of timber structures. If the connections are not modelled accurately, the engineers involved are advised to seek safe sided assumptions regarding them.